Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2002
DOI: 10.1145/503376.503454
|View full text |Cite
|
Sign up to set email alerts
|

Sotto voce

Abstract: In addition to providing information to individual visitors, electronic guidebooks have the potential to facilitate social interaction between visitors and their companions. However, many systems impede visitor interaction. By contrast, our electronic guidebook, Sotto Voce, has social interaction as a primary design goal. The system enables visitors to share audio information -specifically, they can hear each other's guidebook activity using a technologically mediated audio eavesdropping mechanism. We conducte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…However, by providing participants in the technology-led walk with individual devices and headphones, they tended to experience the spoken audio in isolation from other participants, turning the group experience into more of a solitary one. This finding has also been reported by researchers on the 'Sotto Voce' project, who attempted to address this by providing shared audio via an 'eavesdropping' mechanism [13].…”
Section: Number Of Participants and Social Interactionssupporting
confidence: 68%
“…However, by providing participants in the technology-led walk with individual devices and headphones, they tended to experience the spoken audio in isolation from other participants, turning the group experience into more of a solitary one. This finding has also been reported by researchers on the 'Sotto Voce' project, who attempted to address this by providing shared audio via an 'eavesdropping' mechanism [13].…”
Section: Number Of Participants and Social Interactionssupporting
confidence: 68%
“…If one visitor chooses a clip, the other can either choose to hear what their companion had selected, or listen to their own. The team found that when visitors could hear what their companionsÕ audio guide was saying, they were much more likely to engage with each other over objects, whether those objects were mentioned directly in the guide or not (Aoki et al, 2002). Fascinatingly, the researchers found that the shared experience shifted the importance from the objects to the space around them, allowing visitors to navigate themselves around the museum rather than being led.…”
Section: Previous Work In Designing Group Experiences With Digital Tementioning
confidence: 99%
“…We here presented benefits of distributed control such as supporting co-experience, fostering the inclusion of companions into the activity and prompting companions to engage with each other socially while using an interactive exhibit. The latter is important to note as there is limited evidence of how to design to support both social interaction between companions and the inclusion of several people in the activity, in the context of museums [4,56] and can often be associated with other tradeoffs [30,66]. Other benefits include adults' physical interaction along with children and shared experiences through different perspectives.…”
Section: Closing Remarksmentioning
confidence: 99%